Impacts of free market and US foreign policy on Colombian and Latin American revolution - Noam Chomsky (Universidad de San Buenaventura, 2015)
After several coups assisted by US agencies since the fifties in Latin America, and deep economic crises in the eighties and the nineties in South America explained by “the rule of markets” enforced by multilateral organizations, the US leadership in the Americas has been lost, and democratic countries have turned against neoliberalism with wide popular support inside a new “South American revolution” with important projects of integration. Colombia has become the capital in South America for US leadership in economics and politics, and the only country that still has guerrillas, paramilitary armies, and internal conflict. What has been the role of the US in Colombian conflict? What is in stake with the new peace process in Colombia? How this process will affect the US leadership in Latin America? These are some questions that will be reviewed by Noam Chomsky, one of the most influential thinkers of our times.